The first experience of applying a new pancreatoenteroanastomosis with a «soft» pancreatic stump in pancreatoduodenal resection - A. Yu. Barannikov; V. D. Sakhno; V. M. Durleshter; A. V. Andreev; E. V. Tokarenko (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to improve the results of pancreatoduodenal resection by reducing the incidence of pancreatoenteroanastomotic leak and postoperative pancreatitis with a «soft» pancreatic stump.METHODS AND MATERIALS. A new method for the formation of pancreatoenteroanastomosis has been developed and implemented: precision wirsungojejunoanastomosis with additional wide atraumatic peritonization of the pancreatic stump cutoff with the loop of the small intestine. From February 2016 to March 2018, this method was tested in 18 patients.RESULTS. Pancreatoenteroanastomotic leak of class A was noted in 2 (11.1 %) patients, was transient, asymptomatic, did not require additional medical measures and did not extend the duration of the postoperative period. There were no pancreatoenteroanastomotic leak of classes B and C, pancreonecrosis of the stump, lethal outcomes. Objectively worst statistical results were obtained in the comparison group.CONCLUSION. The formation of the small intestine anastomosis with a «soft» pancreatic stump according to the proposed method for pancreatoduodenal resection reduces the incidence of postoperative pancreatitis of the stump and pancreatoenteroanastomotic leak.